2005
DOI: 10.1002/cbdv.200590039
|View full text |Cite
|
Sign up to set email alerts
|

The Proteolytic Stability of ‘Designed’β-Peptides Containingα-Peptide-Bond Mimics and of Mixedα,β-Peptides: Application to the Construction of MHC-Binding Peptides

Abstract: Dedicated to Professor Piero Salvadori, University of Pisa, on the occasion of his 70th birthday Whereas a-peptides are rapidly degraded in vivo and in vitro by a multitude of peptidases, substrates constructed entirely of or incorporating homologated a-amino acid (i.e., b-amino acid) units exhibit a superior stability profile. Efforts made so far to proteolytically hydrolyze a bÀb peptide bond have not proved fruitful; a study aimed at breaching this proteolytic stability is discussed here. A series of such b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 81 publications
3
98
0
1
Order By: Relevance
“…S8A). It has been proposed that the introduction of β-amino acids into the peptides provides increased resistance to hydrolysis and contributes to their stability in biological systems (32,33). Additionally, the gichigamins lack both glutamine (Gln) and glutamic acid (Glu) residues, which Ac U P U P F J…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8A). It has been proposed that the introduction of β-amino acids into the peptides provides increased resistance to hydrolysis and contributes to their stability in biological systems (32,33). Additionally, the gichigamins lack both glutamine (Gln) and glutamic acid (Glu) residues, which Ac U P U P F J…”
Section: Resultsmentioning
confidence: 99%
“…The resulting products were purified, structurally characterized, and tested for cytotoxicity to gain further insights into the relationships between the primary and secondary structural features of the gichigamins and their biological properties. Nine major products were obtained (24)(25)(26)(27)(28)(29)(30)(31)(32) from the hydrolysis of 1 (SI Appendix, Fig. S3A) and ECD spectra were collected and analyzed for each compound (SI Appendix, Fig.…”
Section: Partial Hydrolysis Of Gichigamins Reveals Structural Requirementioning
confidence: 99%
“…With the high sensitivity of MALDI MS in ␣ the peptide mass range, it is an obvious choice to apply MALDI MS imaging to the study of the distribution of ␤-peptides as reported here. We therefore chose two ␤ peptides (Figure 1), formerly used in the study of class 1 MHC peptide mimics, as representative examples of a ␤-and an ␤ ␣-peptide ␣ [12].…”
mentioning
confidence: 99%
“…␤ ␤ hLys-OH) was prepared by solid-phase-peptide-synthesis according to [12]. ␣-Peptide ␣ ␣ 2 (Rheuma peptide Ser-Arg-His-His-Ala-PheCys-Phe-Arg) was purchased from NeoMPS (San Diego, CA).…”
mentioning
confidence: 99%
“…29 Furthermore, proteolytic enzymes cannot recognize -peptides [30][31] and the replacement of around 30% of the residues to -amino acids in a peptidic sequence dramatically increases the stability against proteases. [32][33][34] Pharmacokinetic studies revealed elimination half-lives of 3-10 h which is significantly longer than that of an -peptidic sequence. proteogenic side-chain on the  or  carbon atom respectively, and the synthesis of these building blocks are generally straightforward.…”
Section: -Peptide Foldamersmentioning
confidence: 99%